Purchasing Strategies and Performance of Small and Medium-Sized Enterprises in the Manufacturig Sector in Kelantan - Milawati, Mohd. Nawi (2003)
Although the literature suggests increase interest on the effect of purchasing strategy on the performance of firms, empirical studies that emphasized on purchasing strategy and the performance of small and medium-sized enterprises (SMEs) remain limited. This study attempts to address this issue. Based on a sample survey, this study examined the relationship between purchasing strategy and the performance of 92 SMEs. The results of the study indicate significant relationships between single and multiple sourcing strategies and the performance of the SMEs surveyed.